Analysis of Predisposing Factors Affecting Community Participation in COVID-19 Vaccination - Bambang Pujianto; Dian Isti Angraini; Aila Karyus (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). As of June 29, 2022, there were 542,188,789 cases of COVID-19 in the world, and 6,339,275 people died. Recipients of the COVID-19 vaccine in Central Lampung District dose 1 were 898,900 (81.95%) of the 80% target. Those who received the 2nd dose vaccine were 683,002 (62.27%) of the 70% target and booster vaccines by 23,665 (2.16%) of the 40% target. The study aimed to analyze the predisposing factors that influence participation in the COVID-19 vaccination in the community in Central Lampung district in 2022.Subjects and Method: A cross-sectional study was conducted in three sub-districts of Central Lampung district from July to September 2022. A total of 110 people were selected for this study. The dependent variable was the decision of participating in the COVID-19 vaccination. The independent variables were Knowledge, Education, Attitudes, Health Information, and Trust. Data was collected by using a questionnaire. Data were analyzed using a logistic regression test.Results: Health information (aOR= 18.58; 95% CI= 1.83 to 188.05; p= 0.013), and level of trust (aOR= 18.54; 95% CI= 2.77 to 123.80; p= 0.003) were related to community participation in the COVID-19 vaccination.Conclusion: Health information and public trust related to participation in the COVID-19 vaccination in the community. Keywords: predisposing factors, behavior, COVID-19 vaccination.Correspondence:Bambang Pujianto. Masters Program in Public Health, Faculty of Medicine, Universitas Lampung, Indonesia. Jl. Prof. Dr. Ir. Sumantri Brojonegoro No.1, Gedong Meneng, Rajabasa, Bandar Lampung, Indonesia. 35141. Email: pujiantob73@gmail.com. Mobile: +6285840346246. Journal of Health Promotion and Behavior (2023), 08(01): 44-52DOI: https://doi.org/10.26911/thejhpb.2023.08.01.06